'It's just because we're girls': How female students experience and negotiate masculinist school sport. Issue 3 (3rd July 2017) - McSharry, Majella
Abstract : This article focuses on the inequalities experienced particularly by girls who attend co-educational secondary schools where specific male sports dominate school life. The research was undertaken in the Republic of Ireland in three schools known for the participation and success of boys' teams in Gaelic football, hurling and rugby. Through a Bourdieusian account of 'masculine domination', this article examines how girls (and some boys) attending these schools have experienced inequalities in obtaining recognition in sport, and discrimination in accessing male-orientated sports, as well as unequal opportunities, resources and support. School management, teachers and students (both male and female) will be shown to often protect this male preserve by strategies that maintain the exclusion of girls through the normalisation of gender binaries. The article will also show how girls reflect upon their experiences and attempt to mobilise change.